2019
DOI: 10.1590/1678-4324-2019180198
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-melanogenesis Activities of Some Selected Brown Macroalgae from Northern Coasts of the Persian Gulf

Abstract: Melanogenesis is a biological process which led to the synthesis of melanin pigment. Abnormal melanin production results in melasma, solar lentigo, post inflammatory melanoderma, etc. In this study, we examined the potential inhibitory effects of 17 brown macroalgae from Persian Gulf on melanogenesis. The effects of various concentrations (100, 250 and 500 µg/mL) of methanolic extracts of macroalgae belonging to four genera (including: Padina, Colpomonia, Cystoseira and Sargassum) were studied on oxidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
(29 reference statements)
2
9
0
Order By: Relevance
“…Similar results obtained by Namjooyan et al. (2019) showed that P . australis possessed significant inhibitory effect against tyrosinase.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results obtained by Namjooyan et al. (2019) showed that P . australis possessed significant inhibitory effect against tyrosinase.…”
Section: Resultssupporting
confidence: 90%
“…The crude extract, nhexane and aqueous fractions exhibited lower inhibitory activities of 0.09 mg AAE/g, 0.20 and 3.64 mg AAE/g, respectively. Similar results obtained by Namjooyan et al (2019) showed that P. australis possessed significant inhibitory effect against tyrosinase. The high amount of TPC found in EA fraction may have a link with its strong tyrosinase inhibitory activity (Wang et al, 2014;Xue et al, 2011;Yoon et al, 2009).…”
Section: Recovery Yield Tpc Antioxidant and Tyrosinanse Inhibitory Activities Of P Australis Crude Extract And Fractionssupporting
confidence: 84%
“…Sargassum silquastrum, Ecklonia cava, Schizymenia dubyi, and Endarachne binghamiae have been proven to have tyrosinase inhibitory effect similar to that of kojic acid [29] . Digenea simplex, Laurencia papillosa, and Laurencia paniculata indicated a significant inhibitory effect on monophenolase and diphenolase (of mushroom tyrosinase) in zebrafish model compared to kojic acid [30] .…”
Section: Butanamidsmentioning
confidence: 94%
“…The production of melanin pigment is controlled by a key enzyme known as tyrosinase, and natural algal inhibitors of this enzyme could be used in pharmaceutical and cosmetic industries to prevent and/or treat excessive production of melanin. In this regard, one study investigated the in vitro antityrosinase and in vivo antimelanogenic activities of the methanolic extracts of three red macroalgae, Digenea simplex, Laurencia papillosa, and L. paniculata (the last two species are currently known as Palisada papillosa and P. paniculata, respectively) from the Persian Gulf (Namjoyan et al, 2019). The latter Laurencia species are the first to be described for their remarkable antityrosinase activity (43.18%) and the ability to decrease total melanin content by 47.27% in zebrafish (in vivo model tested), indicating that such ability supports their use as whitening agents to treat hyperpigmentation diseases.…”
Section: Polyphenolics (Phenolic Acids and Flavonoids)mentioning
confidence: 99%